A re-description of Longicyatholaimus maldivarum Gerlach, 1964 (Nematoda, Cyatholamidae) with an emended identification key of the genus - Semprucci, F.; Burattini, S.; Falcieri, E.; Balsamo, M. (Zootaxa, 2017)
Longicyatholaimus maldivarum was a species erected by Gerlach in 1964 from specimens found in the Maldivian archipelago. Due to the finding of additional representatives of this species, L. maldivarum is re-described with the addition of new morphological details mainly about males, because the information about female in the original description are very scarce. The newly found specimens showed a total body length higher than in the type specimens (1936–2063 µm vs. 1330 µm long) as well as the ratio of the total body length divided by maximum body diameter (22–28 vs. 27). The multispiral amphideal fovea showed 5 turns vs. 4 turns and Gerlach did not notice the presence of sub-ventral teeth that were clearly observed in the present specimens. The copulatory apparatus that perfectly matched the Gerlach description showed a central lamella mainly visible under confocal microscopy. A slightly lower ratio of the spicule length divided by anal body diameter (1 vs. 1.4) and longer gubernaculum (25–32 vs. 25 µm long) were noticed as well. Pre-cloacal supplements appeared very interesting for the presence of stout and conical setae protruding from cup-shaped structures. Supplements were more than in type species (8–9 vs. 7). Also the tail revealed some differences with a lower ratio of its total length divided by anal body diameter 6 vs. 7–8. The current list of 15 valid species of the genus was reduced to 10 species. In detail, we considered Longicyatholaimus heterurus and Longicyatholaimus sp. 3 species inquirendae for the absence of male specimens in the original description. We also excluded L. filicaudatus and L. tenuicaudatus because they were considered species inquirendae by Wieser & Hopper (1967) and L. zosterae because it was transferred by Lorenzen (1972) to the genus Paralongicyatholaimus. The new morphological details observed for Longicyatholaimus maldivarum and the modified number of valid species of the genus required also a revision of the identification key.